Analisis Faktor-faktor Produksi Yang Mempengaruhi Pendapatan Petani pada Usahatani Kentang Varietas Granola di Probolinggo - Novita Lidyana; Retno Sulistiyowati (Universitas Islam Kadiri, 2022)
The purpose of this study is to determine the factors of production that affect the income of farming businesses. The factors of production used are the cost of production used, land area and labor use. The data of this study were carried out in a primary and secondary manner. Primary data was conducted by interview with Granola Potato farmers in Sumber District, Probolinggo Regency while secondary data was obtained from related agencies. The data analysis method used uses quantitative descriptive methods. The results obtained from this study are (1) The total cost with the average production of potato harvests of 19,000 kg is Rp.57,205,000 generated by the Granola variety potato farming income of Rp.105,295,000. (2) Variables of arable land area (X1) and labor (X3) partially affect positively and significantly affect the income of Granola Potato farmers. Meanwhile, the variable cost of production (X2) has a negative and insignificant effect. (3) Variables of arable land area (X1), production costs (X2) and labor (X3) simultaneously have a positive and significant effect on the income of Granola Potato farmers in Sumber District, Probolinggo Regency Keywords: Production factors: income: Granola potato farmers